Previous self-stresses creation methods review in bent steel reinforced concrete structures with solid cross section - Hasenko, Anton (Academic journal Industrial Machine Building Civil Engineering, 2022)
Bent steel reinforced concrete structures are usually structures for overlap or covering buildings and constructions for various functional purposes. Pre-stresses in structures of this type can be created by installing additional pre-stressed reinforcing bars in the stretched cross-sectional area, which, along with increasing the load-bearing capacity and stiffness of the floors, requires additional material costs and the installation of these bars. Creating initial stresses in building structures from their own weight greatly simplifies the process of pre-stressing due to the unnecessary cost of additional measures and adaptations. Preliminary stresses, in this case, can be created due to the well-chosen sizes of the nodes and the development of technology for the preliminary assembly of building structures. Therefore, the purpose of research is to generalize the design features and principles of bent reinforced concrete structures with solid cross-section parts pre-stressing and separation among them and to develop new effective methods of creating pre-self-stresses - pre-internal stresses opposite to those arising during operation
Keywords: self-stress; steel-concrete composite structures; construction; nodes; technology